Tingkat Kepuasan Pasien/Keluarga Pasien terhadap Kualitas Pelayanan di Pendaftaran Rawat Inap UPT RSUD RAA Soewondo Pati Tahun 2023 - Miftahul Yaris Widyaningtyas; Maulina Latifah; Cahyono Rahadiyanto; Natalia Kristiani (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2024)
From the results of interviews, there were still patients/patients' families who were not satisfied with TPPRI services because the speed and service skills of registration officers were still slow in serving registration. The aim of this research is to determine the level of satisfaction of patients/families of patients who register for inpatient registration based on five dimensions. This research uses descriptive research using a quantitative approach. The sample size used was 100 patients/families. The sampling technique used is Incidental Sampling. Collection methods are primary data and secondary data. The results of research on the level of satisfaction of patients/patients' families at the UPT inpatient registration at RSUD RAA Soewondo Pati based on five dimensions show that the level of patient satisfaction in the Tangibles dimension is 63.3%, the reliability dimension is 81.5%, the responsiveness dimension is 82.7%, the empathy dimension 84.4%, and the assurance dimension 87.6%. So the average percentage score for overall patient satisfaction is 79.9% with the satisfaction classification being satisfied. Researchers suggest that there is a need for facilities such as television, magazines, newspapers and wifi so that patients/patients' families do not get bored while waiting to register, providing cell phone chargers and drinking water. Comfortable room temperature/humidity temperature in the room must be taken into account so that the room is not hot by adding air conditioning in the registration waiting room to make it more comfortable, sequence numbers are provided for patients from the emergency room and outpatient patients, officers recheck patient data according to the patient's identity (KTP) and verify the data with the person registering so that no errors occur, and the officer gives the patient/patient's family the opportunity to ask again about information that is not understood.